Hemodynamic Effects Of Intravenous Magnesium Sulfate In Direct Laryngoscopy And Intubation In Elective Surgery - Khan, Rashid Ullah; Bilal, Muhammad; Amjad, Mishal; Zareen, Abeera; Rahna, Afia; Iqbal, Javed (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the efficacy of 20 mg/kg of IV MgSO4 in blunting laryngoscopic stress response. Methodology: A single-blind randomized control trial was carried out Department of Anesthesia and Critical Care Medicine, Pakistan Institute of Medical Sciences (PIMS), Islamabad. 122 patients were included and divided into two groups with the help of computer-generated random numbers. Group A patients received 20 mg/kg of MgSO4 while group B patients received a similar volume of Normal saline. Baseline hemodynamics were recorded. General anaesthesia was induced in both groups using Midazolam, Propofol and Atracurium given IV. Following intubation hemodynamics were noted. Results: Baseline parameters and hemodynamics following intubation were similar in both groups apart from DBP in the immediate post-intubation period which was lower in group A. Conclusion: IV MgSO4 at a dose of 20 mg/kg is ineffective in blunting laryngoscopic stress response. Therefore, higher doses should be utilized to reach this therapeutic effect.